PENGARUH KEPEMILIKAN INSTITUSIONAL, DEBT COVENANT, UKURAN PERUSAHAAN, DAN GROWTH OPPORTUNITY TERHADAP KONSERVATISME AKUNTANSI INDUSTRI MANUFAKTUR - Budiman, Theresia Widyawati; Pambudi, Rilo (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2024)
This study examines and explains the effect of institutional ownership, debt covenants, company size, and growth opportunities on accounting conservatism in non-cyclical consumer sector manufacturing companies. The type of research used to process 120 non-cyclical consumer sector manufacturing companies with data in 2018-2023 is quantitative research. This study uses secondary data in the form of financial reports and company annual reports. The data is processed using IBM SPSS Statistics 25 software with testing methods including descriptive statistical analysis, classical assumption tests, multiple regression analysis, and hypothesis testing. The results of this study indicate that institutional ownership, company size, and growth opportunities do not affect accounting conservatism, while debt covenants affect accounting conservatism. Based on the results of this study, debt covenants can affect accounting conservatism, help managers design more prudent accounting policies, and avoid financial or legal costs due to covenant violations. Understanding how debt covenants can affect accounting conservatism helps managers design more prudent accounting policies, especially for companies with large loans or debts. This can help reduce the risk of mismanagement that could harm the company.